Optical and EPR studies of zinc phosphate glasses containing Mn2+ ions - Franco, Douglas F. [UNESP]; Manzani, Danilo; Carvajal, Eduar E.; Prando, Gabriela Augusta; Donoso, José Pedro; Magon, Claudio J.; Antonio, Selma G. [UNESP]; Gobato, Yara Galvão; Nalin, Marcelo [UNESP] (Springer Nature, 2020)
A set of glass samples with composition based on ternary 50P2O5–30Na2O–20ZnO (PNZ) matrix doped with different MnO contents was prepared via melt-quenching technique. Thermal, structural and spectroscopic properties were investigated by differential scanning calorimetry (DSC), X-ray powder diffraction (XRD), Raman spectroscopy, UV–visible absorption, photoluminescence (PL) and by electron paramagnetic resonance (EPR) using Mn2+ as probe. Glass compositions (100-x)PNZ:xMn (0.01 ≤ x ≤ 1.0 in mol% of MnO) were characterized as glasses after careful analysis of the thermal and structural data. While DSC curves show the presence of the glass transition phenomenon (Tg), XRD analysis identified the non-crystalline arrangement, compatible with glass structure. Raman spectra of PNZ:xMn samples showed that the successive increase in Mn2+ content leads to rise of vibrational modes assigned to phosphate Q1 units, suggesting the breakdown of phosphate glass network chains. UV–Vis absorption spectra of glasses presented absorption bands centered at 250, 318, 341, 358 and 408 nm attributed to the Mn2+ electronic transitions. Glass samples containing above 0.06 mol% of MnO presented a broadband absorption centered at 511 nm assigned to the presence of traces of Mn3+. Additionally, UV–Vis, PL and EPR data showed that Mn2+ ions are occupying octahedral arrangements. Besides, EPR results suggest that the increase in MnO concentration influences on the EPR signal and hyperfine splitting constant suggests the presence of a moderately ionic bond between Mn2+ and PNZ glass network.